Analysis of Themes and Rhemes Used in Online Covid-19 Vaccine Related News - Alifia, Afifah; Zaim, M. (Universitas Negeri Padang, 2021)
This research aimed at finding the types of themes and elements of theme used in multiple themes on the covid-19 vaccine news item. This research used the descriptive method. The data were news items that discuss the covid-19 vaccine online news on nbcnews.com in January to May 2021. The researcher found four types of themes in news items. They are simple unmarked theme, simple marked theme, multiple unmarked theme, and multiple marked theme. Meanwhile, the element of theme used in multiple theme are conjunction, conjunctive, continuative, wh-relative, finite, modal adjunct, and wh-question. The researcher found that the most dominant type of theme used was the unmarked theme (simple unmarked theme and multiple unmarked theme). This shows that the news is delivered with clear information that focuses on the events in the news.